PENGARUH PENAMBAHAN AKTIVATOR ZnCl2, KOH, DAN H3PO4 DALAM PEMBUATAN KARBON AKTIF DARI PELEPAH AREN (Arenga Pinnata) - Marina Olivia Esterlita, Netti Herlina (Jurnal Teknik Kimia USU, 2015)
This research aimed to determine the effect of carbonization temperature and activator agent in making activated carbon, and also determine the optimum temperature, and best activator agent. The raw material used is kind of lignocellulosic like palm frond. The palm fronds cleaned and chopped, then it soaked in each activator solution include KOH, ZnCl2, and H3PO4 at room temperature for 24 hours. After that, palm fronds carbonized in the furnace at a temperature of 4000C, 5000C, and 6000C in 1 hour. Carbon washed by aquadest until its netral, after that calculated the yield of charcoal, moisture content, and absorption ability of the iodine solution. The highest yield obtained in the activated carbon which impregnated by ZnCl2 at the temperature 4000C which is 82,04%. The best water content of activated carbon obtained in the activated carbon impregnated by H3PO4 of 6% which is the lowest one. Activated carbon which has the largest number of iodine absorption was also obtained on the active carbon carbonized at a temperature of 5000C and activated by H3PO4 which is 767.745 mg iodine / g of activated carbon, and the value is in compliance with SNI.